The Effect of Dialectical Behavior Therapy Techniques Training with lavender Aromatherapy on Depression and Maternal Competence of Nulliparous Women with Insecure Attachment to Spouse - Elham Zameni; Fatemeh Shahabizadeh; Jalil Jarahi Feriz; Nahid Ghanbarzadeh (Hamadan University of Medical Sciences, 2021)
Background and Objective: Pregnancy is one of the most stressful stages in Women's life. The purpose was to determine the effectiveness of Dialectical Behavior Therapy Techniques Training lavender aromatherapy on depression and maternal competence of Primiparous women with Insecure Attachment to Spouse. Material and Methods: This clinical trial study was performed in 2021 on 60 pregnant women in Birjand, Iran. Insecure attached expectant mothers were selected by purposive sampling method and randomly divided between three intervention groups 1 (Dialectical behavior therapy techniques training and aromatherapy), intervention group 2 (aromatherapy with lavender), and control group. Dialectical behavioral therapy techniques were performed in the last three months of pregnancy, aromatherapy in the active phase of labor, and the follow-up period one month after the baby's birth. The attachment to spouse Questionnaire, depression Beck, postpartum depression, and maternal competency were used. Data were analyzed in SPSS 25. Results: The results of repeated analysis of variance showed that teaching dialectical behavioral therapy techniques was effective in reducing depression over time (P<0.001). Covariance analysis showed that depression during pregnancy was decreased significantly after the Dialectical Behavior Therapy Techniques Training (P<0.001). The multivariate analysis of variance also showed both components of maternal competence increased significantly in intervention groups 1 (P<0.05). Conclusion: Dialectical behavioral therapy techniques and aromatherapy are effective interventions to reduce depression and increase maternal competence. They can be used for pregnant women with insecure attachment to their husbands in health centers.